Adsorption of H2S on graphane decorated with Fe, Co and Cu: a DFT study. Issue 50 (19th June 2017) - Zhou, Qingxiao; Su, Xiangying; Ju, Weiwei; Yong, Yongliang; Li, Xiaohong; Fu, Zhibing; Wang, Chaoyang
Abstract : Herein, density functional theory (DFT) calculations were performed to investigate the adsorption of a H2 S molecule on the surface of hydrogenated graphene (graphane). Abstract : Herein, density functional theory (DFT) calculations were performed to investigate the adsorption of a H2 S molecule on the surface of hydrogenated graphene (graphane). In our results, we found that the appearance of an H-vacancy significantly improved the reactivity of graphane due to the unpaired electrons of the vacancy site. However, small adsorption energy and low charge transfer indicated that the interaction between the H2 S molecule and the pure H-vacancy-defected graphane occurred via physisorption. By introducing transition-metal dopants (Fe, Co, and Cu), the adsorption process of the H2 S molecule changed to chemisorption. Furthermore, the adsorption of H2 S induced a decrease in the band gaps, which could be seen as signal for the detection of H2 S gas.